Electrochemical platform based on nitrogen-doped graphene/chitosan nanocomposite for selective Pb2+ detection. (9th February 2017) - Magerusan, Lidia; Socaci, Crina; Coros, Maria; Pogacean, Florina; Rosu, Marcela Corina; Gergely, Stefan; Pruneanu, Stela; Leostean, Cristian; Pana, Ioan Ovidiu
Abstract: A novel nanocomposite was developed and used for trace determination of Pb 2+ cations from aqueous solutions. The nanocomposite was obtained by the association of N-doped graphene (N-Gr) with a biocompatible polymer, namely chitosan (Ch). The characterization of the new nanocomposite material (Ch-N-Gr) was performed using TEM, STEM-EDX, SEM, XRD and XPS techniques. Compared with the bare gold electrode (GE) a remarkable enhancement of the voltammetric response of the modified electrode (Ch-N-Gr/GE) was always observed. Using the Ch-N-Gr/GE, the Pb 2+ voltammetric response showed a pair of well defined, quasi-reversible anodic and cathodic peaks, with the peak potentials located at about −0.59 V and −0.69 V, respectively. The calibration curves were obtained over a large linear range, from 10 −7 to 10 −4 M Pb 2+ concentration. Under optimized conditions, the detection limit was found to be 6.64 × 10 −8 M. The effect of several interfering species (such as other metallic cations or organic compounds of various concentrations) on the determination of Pb 2+ concentration was also studied, and the results proved the selectivity of the proposed modified electrode. The validity and effectiveness of the method was further confirmed by trace determination of Pb 2+ in real samples.